2009
DOI: 10.1007/s11618-009-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Intercoder-Reliabilität bei der Berufscodierung nach der ISCO-88 und Validität des sozioökonomischen Status

Abstract: Intercoder-reliability for coding occupations according to ISCO-88 and the validity of socio-economic status Abstract: Indicators of social background belong to the standard set of instruments for empirical research in education. Construction of valid ranking scales and category systems for social background depends on a differentiated surveying of the occupation and vocational activity of parents. Coding such details using standard procedures is a complex process. This contribution investigates the intercoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
(2 reference statements)
0
10
1
1
Order By: Relevance
“…Additionally, we argue that in the cases where the choice between different codes is hard to make, the occupations in question are more similar with respect to prestige and SES than a randomly chosen pair of occupations would be. In a study by Maaz et al (2009), occupational information was coded by professional coders and lay coders (trained student assistants). The level of consistency between these codings was generally not as high as desirable.…”
Section: Challenges Of Occupation Coding and Previous Researchmentioning
confidence: 99%
“…Additionally, we argue that in the cases where the choice between different codes is hard to make, the occupations in question are more similar with respect to prestige and SES than a randomly chosen pair of occupations would be. In a study by Maaz et al (2009), occupational information was coded by professional coders and lay coders (trained student assistants). The level of consistency between these codings was generally not as high as desirable.…”
Section: Challenges Of Occupation Coding and Previous Researchmentioning
confidence: 99%
“…To ensure high data quality, researchers from various countries have discussed and compared various procedures for occupation coding (Biemer and Caspar, 1994;Campanelli et al, 1997;Bushnell, 1998;Biemer and Lyberg, 2003;Maaz et al, 2009;Svensson, 2012;Belloni et al, 2016). Although they focused on errors that arise from coding after the interview, all these researchers also observed that insufficient, low quality verbal answers from the interview are another possible source of errors.…”
Section: Motives For Interview Codingmentioning
confidence: 99%
“…Though some attempts have been made to improve automated coding for ISCO (see Hoffmeyer-Zlotnik et al 2004, Hoffmeyer-Zlotnik and Warner (2012)), the rule-based method currently employed by Geis (2011) has a production rate lower than 50% and manual checking is intended. The quality for coding according to the ISCO-88 classification (390 categories) has been investigated by Maaz et al (2009). In their study, two professional institutes and two research assistants without prior coding experiences have coded occupations from the parents of 300 high school graduates.…”
Section: Quality Of Occupation Codingmentioning
confidence: 99%